Pandangan dari Tudor City, New York (Shah Alam, Selangor Darul Ehsan, Malaysia Times Editions, 2004)
Sociopolitical issues in Malaysia and other countries; collected articles previously published in Utusan Malaysia newspaper from 1996 to 2000.